Angiotensin II-induced endothelial dysfunction is temporally linked with increases in interleukin-6 and vascular macrophage accumulation - Gomolak, Jessica R.; Didion, Sean P. (Frontiers in Physiology, 2014)
Angiotensin II (Ang II) is associated with vascular hypertrophy, endothelial dysfunction and activation of a number of inflammatory molecules, however the linear events involved in the development of hypertension and endothelial dysfunction produced in response to Ang II are not well defined. The goal of this study was to examine the dose- and temporal-dependent development of endothelial dysfunction in response to Ang II. Blood pressure and responses of carotid arteries were examined in control (C57Bl/6) mice and in mice infused with 50, 100, 200, 400, or 1000 ng/kg/min Ang II for either 14 or 28 Days. Infusion of Ang II was associated with graded and marked increases in systolic blood pressure and plasma Ang II concentrations. While low doses of Ang II (ie, 50 and 100 ng/kg/min) had little to no effect on blood pressure or endothelial function, high doses of Ang II (e.g., 1000 ng/kg/min) were associated with large increases in arterial pressure and marked impairment of endothelial function. In contrast, intermediate doses of Ang II (200 and 400 ng/kg/min) while initially having no effect on systolic blood pressure were associated with significant increases in pressure over time. Despite increasing blood pressure, 200 ng/kg/min had no effect on endothelial function, whereas 400 ng/kg/min produced modest impairment on Day 14 and marked impairment of endothelial function on Day 28. The degree of endothelial dysfunction produced by 400 and 1000 ng/kg/min Ang II was reflective of parallel increases in plasma IL-6 levels and vascular macrophage content, suggesting that increases in arterial blood pressure precede the development of endothelial dysfunction. These findings are important as they demonstrate that along with increases in arterial pressure that increases in IL-6 and vascular macrophage accumulation correlate with the impairment of endothelial function produced by Ang II.